Transgender Erasure: Barriers Facing Transgender Refugees in Canada - Verman, Alex; Rehaag, Sean (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2024)
This paper explores the experiences of transgender refugee claimants in Canada’s refugee status determination system by using mixed methods: quantitative analysis of data obtained from the Immigration and Refugee Board (IRB), reviews of published and unpublished decisions, country condition documentation packages and IRB guidelines, as well as interviews with refugee lawyers. Using these methods, we explore how credibility arises in transgender refugee claims, noting the impact of medicalization and country conditions materials on transgender claims, and drawing parallels between medical gatekeeping and credibility assessments in refugee claims. We identify potential explanations for low recorded numbers of transgender claims as rooted in data-gathering and decision-making practices that are misaligned with transgender experiences, and we offer policy recommendations to overcome this mismatch. Though transgender refugee claims appear to be largely successful in recent years, longstanding patterns of exclusion and erasure as policy nevertheless lead many transgender claimants to experience the refugee determination process as traumatic and transphobic, resulting in unaccounted-for complications and challenges to practice.